Expressão heteróloga da EMA-2 de Theileria equi em Pichia pastoris - Vianna, Ana Muñoz (2011)
The equine piroplasmosis caused by Theileria equi is considered one of the most important equine diseases in both tropical and subtropical countries. Theileriosis is endemic in Brazil and causes significant economic losses for equine breeders. Disease-free countries restrict horse transit coming from endemic areas due to the high prevalence of asymptomatic carrier animals. In order to prevent and control this disease, it is therefore necessary to develop efficient diagnostic methods. Previous Theileria equi immunological diagnostic studies have been based in outer membrane antigens. Equi merozoite antigen (EMA) is a major outer membrane antigen of this protozoan, recognized by antibodies of Theileria equi positive horses. In this study, we reported the expression, purification and characterization of EMA-2 protein of Theileria equi in the yeast Pichia pastoris. The EMA-2 gene was cloned into the expression vector pPICZαB and the expressed protein was secreted to the medium as a soluble form. The expression and antigenicity of rEMA-2 protein was demonstrated by Dot and Western Blotting, using anti-histidine and equine Theileriosis clinically positive antibodies. An indirect ELISA with the rEMA-2 was performed and it was possible to differentiate with more than a threefold difference between negative and positive serum from horses confirmed with Theileriosis. The data obtained in this work suggest that the rEMA-2 protein expressed in P. pastoris is a potential candidate for use as antigen in immunodiagnostic of T. equi.